Reactualization of Islamic Teachings in Indonesia; A Study of Munawir Sjadzali's Islamic Reform Thought - Sutoyib, Niki; Hady, M. Samsul; Wafi, Hasan Abdul (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2024)
This research discusses the re-actualization of Islamic teachings in Indonesia as proposed by Munawir Sjadzali. Munawir Sjadzali was an Indonesian Islamic intellectual and bureaucrat who served as the Minister of Religious Affairs of the Republic of Indonesia for two terms, from 1983 to 1993. The re-actualization of Islamic teachings conducted by Munawir Sjadzali was inspired by the Islamic reform movement previously championed by thinkers and reformers such as Muhammad Abduh and Rasyid Ridho. This study is a type of library research using descriptive-analytical methods. The results of the study reveal that the re-actualization of Islamic teachings from Munawir Sjadzali's perspective does not mean moving Islam away from the axis of classical ijtihad, but rather an effort to ensure that Islamic teachings are always contextual with the conditions of Muslims in Indonesia (shalih likulli zaman wa makan). Specifically, Munawir Sjadzali offers three methods of ijtihad in the reform of Islamic law: first, 'adat, used in issues of inheritance distribution by considering the socio-economic conditions of Indonesian society and the roles of men and women; second, nasakh (abrogation) on issues of slavery that are inconsistent or contradictory to human rights; and third, mashlahah (public interest) on the issue of bank interest. In this regard, Munawir Sjadzali accepts bank interest on the grounds of mashlahah, but he remains accommodative towards the establishment of Bank Mu'amalah and Sharia Rural Banks (BPR Syariah) with the principle of trade partnership while adhering to prevailing banking regulations. Abstrak: Penelitian ini membahas tentang reaktualisasi ajaran Islam di Indonesia yang dikemukakan oleh Munawir Sjadzali. Munawir Sjadzali merupakan seorang intelektual Islam Indonesia sekaligus birokrat yang pernah menjabat sebagai Menteri Agama Republik Indonesia selama dua periode, yaitu tahun 1983 – 1993. Reaktualisasi ajaran Islam yang dilakukan oleh Munawir Sjadzali terinspirasi dari gerakan pembaharuan Islam yang sudah digaungkan oleh pemikir dan pembaharu Islam sebelumnya seperti Muhammad Abduh dan Rasyid Ridho. Penelitian ini merupakan jenis penelitian kepustakaan dengan menggunakan metode deskriptif analitis. Hasil dari penelitian mengungkapkan bahwa reaktualisasi ajaran Islam perspektif Munawir Sjadzali bukan berarti menjadikan Islam keluar dari poros ijtihad klasik, namun upaya agar ajaran Islam selalu kontekstual dengan kondisi umat Islam di Indonesia (shalih likulli zaman wa makan). Secara spesifik Munawir Sjadzali menawarkan tiga metode ijtihad dalam pembaharuan hukum Islam, yaitu; pertama, adat, digunakan pada masalah pembagian harta warisan dengan mempertimbangkan kondisi sosial-ekonomi masyarakat Indonesia serta peran laki-laki dan perempuan; kedua, nasakh pada isu-isu tentang perbudakan yang tidak sesuai atau bertentangan dengan Hak Asasi Manusia (HAM); dan ketiga, mashlahah pada isu bunga bank. Dalam hal ini Munawir Sjadzali menerima bunga bank dengan alasan mashlahah, namun ia tetap akomodatif terhadap pembentukan Bank Mu'amalah dan bank BPR Syariah dengan prinsip kemitraan perdagangan dengan tetap mengindahkan peraturan perbankan yang berlaku.